Image of the Month: Meconium Peritonitis with Pseudocyst—A Spot Diagnosis in Newborns - Ascherl, Rudolph; Vaz Pimentel, Duarte; Knüpfer, Mathias; Sorge, Ina; Lacher, Martin; Zimmermann, Peter (European Journal of Pediatric Surgery Reports, 2020)
We report on a male preterm newborn with a large abdominal tumor found on prenatal ultrasound 2 weeks prior to delivery at 36 + 0 weeks of gestation. A postnatal abdominal plain film showed a mass with well-defined rim calcifications (“eggshell”), suggestive of a meconium pseudocyst. On the 4th day of life, the boy underwent exploratory laparotomy with resection of the cyst and end-to-back jejunojejunostomy. The postoperative course was uneventful. A meconium pseudocyst is the correlate of a sterile peritonitis caused by antenatal bowel perforation. It is an easily recognizable spot diagnosis any pediatrician and pediatric surgeon should be aware of.
Keywords: meconium; pseudocyst; cyst; newborn; calcification